2020
DOI: 10.1108/ijem-07-2019-0237
|View full text |Cite
|
Sign up to set email alerts
|

Factors to improve job performance and school effectiveness

Abstract: PurposeIdentify some of the most relevant factors that trigger a private school's workforce to foster a sustainable competitive advantage by reinforcing the intrinsic job satisfaction and the levels of teacher self-efficacy, engagement and job performance.Design/methodology/approachSurveys were applied to private school teachers to assess their perception concerning the studied variables, data were tested at a confirmatory level using the partial least squares path modelling (PLS-PM).FindingsTeachers with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 80 publications
(126 reference statements)
1
20
0
1
Order By: Relevance
“…Figure 6 reports the factorial loads [λ], highlighting the relative importance of the items that make up each latent variable (Soto-Pérez et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 reports the factorial loads [λ], highlighting the relative importance of the items that make up each latent variable (Soto-Pérez et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested by Story and Castanheira (2019) that the socially responsible company has a substantial positive effect on worker satisfaction, thus producing positive work behavior and organizational outcomes. Furthermore, Soto‐Pérez, Sánchez‐García, and Núñez‐Ríos (2020) research concluded that teachers with a high sense of self‐efficacy and possessing high intrinsic satisfaction tend to be highly productive and results‐oriented. Intrinsic job satisfaction is a crucial factor that influences extrinsic job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, reinforcing previous research, evidence was found that student citizenship behaviour positively influences student in-role performance, with a weight of 0.42 and a p-value < 0.05, allowing confirmation of the H 8 hypotheses. Although the positive relationship in which OCB influences in-role performance has been previously studied and demonstrated in the field of employment (Leung, 2008;Podsakoff et al, 2009;Soto-Pérez et al, 2020), in this case, it has been analysed in the student context. Thus, students who actively participate in the mediation of class conflicts, support their classmates and know how to work in a team also have a higher student in-role performance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, student in-role performance refers to the efficiency with which a student fulfils a subject's curricular map (Abbas et al, 2019;Felfe et al, 2014). Citizenship behaviours are considered to contribute to achieving academic goals and increasing effectiveness in group learning (Leung, 2008), and at the same time having a positive impact on in-role performance (Soto-Pérez et al, 2020). Since student citizenship behaviours also have a positive impact on the community (Morphew & Hartley, 2006), educational institutions have emphasised such behaviours to enhance it, as they can improve the public image of the institution (Meriac, 2012), as well as training professionals who are responsible to society (Shao et al, 2019).…”
Section: Student Performance and Academic Achievementmentioning
confidence: 99%